Saell - a tool to support Libras Studies as a L2 and a learning object for learners and teachers - Silva, Lídia da; da Silva Bento, Juliane (The ESPecialist, 2022)
Digital media stimulate communication and can contribute to the studies of Brazilian Sign Language (Libras) as a second language (L2) for hearing people. This bibliographical work is situated in this context and aims to present the Support System for the Studies of Libras as L2 (Saell) and demonstrate that this site is characterized as a learning object. Therefore, it describes its structure and functioning and proves that it presents granularity, reusability, interoperability, recoverability, interactivity, and autonomy (Gama, 2007; Lebedeff, 2017; Leffa, 2006). Conclusively, it considers that Saell meets the current technological trend in language education; that, through its organization, facilitates the collaboration and sharing of relevant linguistic and pedagogical content; and that, in an original way, initiates contributions to the repositories of didactic and instructional materials in video for learners and teachers who work with Libras as L2.